The Impact of Self-Regulated Learning on the Effectiveness of Digital Learning: A Study on Madrasah Ibtidaiyah Students - Ardiyanti, Vivin; Fauzan, Fauzan; Lestari, Futry Ayu (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractThis study aims to examine the effect of self-regulated learning on the effectiveness of digital learning in fifth-grade students of Madrasah Ibtidaiyah Pembangunan Jakarta, Indonesia. This study employs a quantitative approach using a survey design and a total sampling technique, which involves 67 fifth-grade students as respondents. Data were collected through a validated Likert scale questionnaire designed to measure self-learning variables and the use of digital learning. Simple linear regression testing was implemented to verify the research hypothesis and identify interconnections among variables. Study findings indicate the presence of a meaningful positive impact between self-directed learning and the effectiveness of digital learning, with a coefficient of determination (R²) of 0.366, indicating that 36.6% of the variance in the use of digital learning can be explained by self-regulated learning abilities, while the remaining 63.4% is influenced by other factors not examined in this study. This study concludes that self-regulated learning is an important factor in increasing the effectiveness of digital learning implementation in elementary madrasah students. These findings indicate the importance of developing pedagogical strategies that foster students' self-regulation skills to optimize the integration of digital technology in education environments, especially in madrasah ibtidaiyah.Keywords: digital learning, effectiveness, self regulated learning.AbstrakPenelitian ini bertujuan untuk menguji pengaruh pembelajaran mandiri terhadap efektivitas pembelajaran digital pada siswa kelas V Madrasah Ibtidaiyah Pembangunan Jakarta, Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei dan teknik total sampling yang melibatkan 67 siswa kelas V (lima) sebagai responden. Data dikumpulkan melalui kuesioner skala Likert yang telah divalidasi dan dirancang untuk mengukur pembelajaran mandiri dan penggunaan pembelajaran digital. Pengujian regresi linear sederhana diimplementasikan untuk memverifikasi hipotesis riset dan mengidentifikasi keterkaitan antar variabel. Temuan studi mengindikasikan terdapatnya dampak positif yang bermakna antara pembelajaran mandiri dengan efektivitas pembelajaran digital, dengan koefisien determinasi (R²) sebesar 0,366, yang menunjukkan bahwa 36,6% varians penggunaan pembelajaran digital dapat dijelaskan oleh kemampuan pembelajaran mandiri, sedangkan sisanya sebesar 63,4% dipengaruhi oleh faktor lain yang tidak diteliti dalam penelitian ini. Penelitian ini menyimpulkan bahwa pembelajaran mandiri merupakan faktor penting dalam meningkatkan efektivitas pembelajaran digital pada siswa madrasah ibtidaiyah. Temuan ini menunjukkan pentingnya mengembangkan strategi pedagogis yang menumbuhkan keterampilan pengaturan diri siswa untuk mengoptimalkan integrasi teknologi digital dalam lingkungan pendidikan, khsususnya di Madrasah Ibtidaiyah.Kata kunci: pembelajaran digital, efektivitas, self regulated learning.